The struggle to empower trade union members: insights from Zambia. Issue 8 (16th November 2016) - Finlayson, Caitlin; Palmvang, Maria
ABSTRACT: Empowerment is under-researched in labour and trade unions, not least in sub-Saharan Africa. Based on workplace observations and interviews with union members and staff in agriculture, commerce, and industry, this article shares insights from two trade unions in Zambia. Findings show that the extent of empowerment differs between members and that empowerment is constrained by employer influence, privatisation, lack of government labour law enforcement, and union resources. Using an integrated approach, the article discusses differences in perceptions of empowerment, how external intentions clash with local structures, and offers suggestions which may help to improve union empowerment methods and programmes.